A ação pedagógica sob a perspectiva de Henri Wallon - dos Santos, Elaine Gomes [UNESP]; de Lima, Jose Milton [UNESP] (Universidade Estadual Paulista (Unesp), Instituto de Biociências, 2009)
This research was supported theory as the theory of Henri Wallon which proposes a reflection on the overall development of the child offering subsidies for a acting that values the child in its multiple dimensions. The objective is understood to seek subsidies in theory that can guide the construction of an education in the Children's activites, focused on the development aspects of cognitive, affective and motor of the child. It adopts as methodology the bibliographical revision, the intervention, observation and data collect, using as pedagogic resource playing activities in an institution of Infantile Education. The research noted the possibility of action with the concepts proposed by the Wallonian theory, furthermore, the Children's Fitness, using the recreational activities such as teaching resources boost child development. Therefore, concluded that physical education should include Child in the process of teaching-learning the full development of the child.

Esta pesquisa teve como suporte teórico a Teoria de Henri Wallon a qual propõe uma reflexão acerca do desenvolvimento global da criança oferecendo subsídios para uma atuação que valoriza a criança em suas múltiplas dimensões. O objetivo compreendeu-se em buscar subsídios na teoria walloniana que possam nortear a construção de ações educativas na Educação Física Infantil, voltadas para o desenvolvimento dos aspectos cognitivo, afetivo e motor da criança. Adotou como metodologia a revisão bibliográfica, intervenção, observação e coleta de dados, utilizando como recurso pedagógico as atividades lúdicas em uma instituição de Educação Infantil. A pesquisa constatou a possibilidade de atuação com os conceitos propostos pela teoria walloniana, além disso, que a Educação Física Infantil, utilizando as atividades lúdicas como recursos pedagógicos impulsionam o desenvolvimento infantil. Logo, conclui-se que Educação Física Infantil deve contemplar em seu processo de ensino-aprendizagem o desenvolvimento integral da criança.
The pedagogical action from the perspective of Henri Wallon
Keywords: Henri Wallon; Physical Education; Childhood